Analisis Kemampuan Berpikir Komputasional Mahasiswa Menggunakan GNU Octave - Sahrul Romadona; Yahfizham Yahfizham (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Computational thinking skills are one of the important competencies in the world of education in the 21st century, especially in the fields of science, technology, engineering, and mathematics (STEM). GNU Octave as an open source software similar to MATLAB offers a numeric programming environment that can be used to train and develop students' computational thinking skills. Researchers use a literature study method that aims to see the extent to which GNU Octave can be used in learning to improve students' computational thinking skills. The literature sources used come from national and international journal articles, conference proceedings, and other trusted sources over the past 10 years. The results of the review show that GNU Octave is effective as a learning tool for numeric programming, problem solving, and mathematical modeling, and has a positive contribution to honing students' algorithmic and analytical thinking skills.